Comprehensive Analysis of the Brain-Expressed X-Link Protein Family in Glioblastoma Multiforme - Aisa, Adilai; Tan, Yinuo; Li, Xinyu; Zhang, Ding; Shi, Yun; Yuan, Ying (Frontiers in Oncology, 2022)
Glioblastoma multiforme (GBM) is the most common, malignant, and deadly primary brain tumor in adults. Brain-expressed X-link (BEX) protein family is involved in tumorigenesis. Here, we have explored the biological function and the prognostic value of the BEX family in GBM. Differentially expressed BEX genes between GBM and normal tissue were screened by using The Cancer Genome Atlas (TCGA) database. Univariate and multivariate Cox regression identified the prognosis‐related genes: BEX1, BEX2 and BEX4, which were involved in the regulation of immune response. The results of correlation analysis and protein-protein interaction network (PPI network) showed that there was a significant correlation between BEX family and TCEAL family in GBM. Furthermore, the expression of transcription elongation factor A (SII)-like (TCEAL) family is generally decreased in GBM, and related to poor prognosis. Using the LASSO COX regression, a prognostic model including BEX family and TCEAL family was built to accurately predict the likelihood of overall survival (OS) in GBM patients. Therefore, we demonstrated that BEX family and TCEAL family possessed great potential as therapeutic targets and prognostic biomarkers in GBM. Further investigations in large‐scale, multicenter, and prospective clinical cohorts are needed to confirm the prognostic model developed in our study.